Form and function of conditional constructions in the Gumuz language of Metekel zone - Travis Williamson; Eric Larson (Studies in African Linguistics)
This paper describes not only the forms of the limited number of conditional constructions in Gumuz [guk] but also their various functions as found primarily in natural texts collected from a variety of districts within Metekel Zone in northwestern Ethiopia.